2002
DOI: 10.1073/pnas.052692999
|View full text |Cite
|
Sign up to set email alerts
|

The vitelliform macular dystrophy protein defines a new family of chloride channels

Abstract: Vitelliform macular dystrophy (VMD͞Best disease; MIM*153700) is an early-onset autosomal dominant disorder in which accumulation of lipofuscin-like material within and beneath the retinal pigment epithelium is associated with a progressive loss of central vision. Bestrophin, the protein product of the VMD gene, has four predicted transmembrane domains. There are multiple bestrophin homologues in the human, Drosophila, and Caenorhabditis elegans genomes, but no function has previously been ascribed to these pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
430
2
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(459 citation statements)
references
References 23 publications
26
430
2
1
Order By: Relevance
“…Since LP defects are a characteristic of Best vitelliform macular dystrophy (BMD), a disease caused by mutations in Best-1, it was hypothesized that Best-1 functions as a Ca ++ sensitive Cl − channel (CaCC) that generates the LP. Whole cell patch clamp studies of Best-1 and other bestrophins heterologously expressed in cultured cells support this hypothesis (Sun et al, 2002). Further support comes from experiments in which replacement of key amino acids appears to alter the channel ion selectivity (reviewed in Hartzell et al, 2005).…”
Section: Functionmentioning
confidence: 96%
“…Since LP defects are a characteristic of Best vitelliform macular dystrophy (BMD), a disease caused by mutations in Best-1, it was hypothesized that Best-1 functions as a Ca ++ sensitive Cl − channel (CaCC) that generates the LP. Whole cell patch clamp studies of Best-1 and other bestrophins heterologously expressed in cultured cells support this hypothesis (Sun et al, 2002). Further support comes from experiments in which replacement of key amino acids appears to alter the channel ion selectivity (reviewed in Hartzell et al, 2005).…”
Section: Functionmentioning
confidence: 96%
“…[1][2][3][4][5][6] BEST1 is located on chromosome 11q13 and encodes the bestrophin-1 protein that localizes to the RPE. 1,7,8 The exact function of the bestrophin protein is not completely understood. However, it has been suggested that bestrophin-1 acts as either a chloride channel or a modulator of calcium channels.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been suggested that bestrophin-1 acts as either a chloride channel or a modulator of calcium channels. 6,[8][9][10] To date, several mutations in arBVMD cases have been reported. [1][2][3]5,11,12 These include homozygous and combinations of nonsense or missense mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significance of their conductance in many tissues, the molecular identity for the encoding channel remains unknown. Bestrophins have been identified as a novel family of Cl Ca (46) with multiple members expressed in different species (17). Several Bestrophin members have been shown to produce a calcium-activated chloride current (I ClCa ) when expressed heterologously (30, 33-36, 41, 46, 48, 49).…”
mentioning
confidence: 99%